2022
DOI: 10.3390/biomedicines10081783
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria for Treatment: Microbiome in Bladder Cancer

Abstract: The human body contains a variety of microbes. The distribution of microbes varies from organ to organ. Sequencing and bioinformatics techniques have revolutionized microbial research. Although previously considered to be sterile, the urinary bladder contains various microbes. Several studies have used urine and bladder tissues to reveal the microbiome of the urinary bladder. Lactic acid-producing bacteria, such as Bifidobacterium, Lactobacillus, and Lactococcus, are particularly beneficial for human health an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 88 publications
1
3
0
Order By: Relevance
“…Expanding on this comparison revealed varying trends in Bacteroidetes and Firmicutes abundance in patients with NAFLD across geographical regions, highlighting the potential influence of dietary habits on the gut microbiota composition. Interestingly, we observed an enrichment of lactic acid-producing bacteria (such as Lactobacillus) in patients with NAFLD, consistent with the microbiome results reported by Min et al (2022) in patients with bladder cancer. Although there is an association between NAFLD and bladder cancer (Bjorkstrom et al, 2022), the complex mechanisms through which NAFLD promotes the occurrence of bladder cancer remain to be fully elucidated.…”
Section: Discussionsupporting
confidence: 91%
“…Expanding on this comparison revealed varying trends in Bacteroidetes and Firmicutes abundance in patients with NAFLD across geographical regions, highlighting the potential influence of dietary habits on the gut microbiota composition. Interestingly, we observed an enrichment of lactic acid-producing bacteria (such as Lactobacillus) in patients with NAFLD, consistent with the microbiome results reported by Min et al (2022) in patients with bladder cancer. Although there is an association between NAFLD and bladder cancer (Bjorkstrom et al, 2022), the complex mechanisms through which NAFLD promotes the occurrence of bladder cancer remain to be fully elucidated.…”
Section: Discussionsupporting
confidence: 91%
“…Recent evidence suggests that lactic acid-producing bacteria may have therapeutic value in augmenting immunotherapy response in bladder cancer. The presence or addition of Bifidobacterium and Lactobacillus genera in the bladder has been shown to induce apoptosis and provide antitumor properties through immune-mediated mechanisms [ 50 ]. Lactobacillus rhamnosus and Lactobacillus casei have specifically demonstrated anti-proliferative effects on bladder cancer cell lines in vitro and in vivo mouse models; in one study, Lactobacillus casei was even more cytotoxic to bladder cancer cells than BCG because it directly induced necrosis [ 51 , 52 ].…”
Section: Methodsmentioning
confidence: 99%
“…Recent evidence suggests that lactic acid-producing bacteria may have therapeutic value in augmenting immunotherapy response in bladder cancer. The presence or addition of Bifidobacterium and Lactobacillus genera in the bladder has been shown to induce apoptosis and provide antitumor properties through immune-mediated mechanisms [50].…”
Section: The Microbiome and Immunotherapy Response In Bladder Cancermentioning
confidence: 99%
“… 42 The urinary microbiome may play a role in predicting responsiveness to BCG therapy for NMIBC, especially since numerous studies have identified changes in the diversity and abundance of bacteria in the bladder among patients with urothelial carcinoma compared to healthy controls. 43 Several of these studies also demonstrated that certain lactic acid-producing bacteria (such as Lactobacillus rhamnosus and Lactobacillus casei ) have anti-proliferative effects on bladder cancer cell lines in vitro and in vivo mouse models. 44 , 45 Additionally, in a trial of 31 patients treated for NMIBC with intravesical BCG immunotherapy, Sweis et al reported higher relative concentrations of Proteobacteria in patients with tumor recurrence ( P = .035), whereas Lactobacillales were more abundant in patients without tumor recurrence ( P = .049).…”
Section: Applications To Urothelial Carcinomamentioning
confidence: 99%